Prevalence and correlates of mental illness among inmates in North-western Ethiopia: A new look into the roles of rehabilitation service use - Yesuf, Yassin Mohammed; Birhan, Amlaku Alemu; Birara, Addisu Gedlu; Adimas, Bewket Dereje; Bezabh, Abebe Bahiru; Agmase, Nega Gedefaw (Frontiers in Psychiatry, 2022)
Data on the magnitude of mental illnesses and associated factors among inmates in Ethiopia, in general and in the Amhara region in particular are scarce. The available studies either focused on specific type of mental illness or include inmates from a single correctional center and leave aside the role of rehabilitation service use in inmates’ mental illness. Therefore, the present study was conducted to look into the prevalence of mental illnesses and to examine the associated demographic, imprisonment related and rehabilitation service use related factors among inmates in Northwestern Ethiopia. The study employed cross-sectional, descriptive and explanatory research design where data was collected from 422 inmates from three randomly selected prisons. Inmates’ mental illness was assessed using the Self Reporting Questionnaire (SRQ-20). Frequency, percentage, bivariate and multiple logistic regressions were used to analyze the collected data. In the study it was revealed that 74.6% of the inmates in Northwestern Ethiopia have mental illnesses. Feeling unhappy, difficulty to play important role in life, headaches and bad sleep were experienced by majority of the respondents. Male inmates (AOR = 2.39, 95% CI = 1.07–5.37) and inmates who participate in the educational training services (AOR = 2.20, 95% CI = 1.36–3.55) were found to have higher chances of having mental illnesses. On the other hand, inmates who participate in life skill training programs (AOR = 0.45, 95% CI = 0.28–0.74) and inmates who participate in recreational and cultural activities (AOR = 0.26, 95% CI = 0.14–0.46) were found to have lower odds of developing mental illnesses. A high prevalence of mental illnesses among inmates was found in Northwestern Ethiopia and inmates’ participation in rehabilitation services were important correlates of their mental health. Thus, prison administrators and policy makers need to conduct large scale studies and develop tailored interventions that could reform the rehabilitation services provisions, including mental health service provisions.